PENYULUHAN PENTINGNYA PEMBERIAN IMUNISASI DASAR LENGKAP PADA BAYI USIA < 12 BULAN DI WILAYAH KERJA BIDAN PRAKTIK MANDIRI ATLANTIKA AMD.KEB TANGKI SERIBU KOTA BATAM - Indah Mastikana; Akmalia Ayunita Purnomo; Rana Prasenja Sahara (LPPM Universitas Awal Bros, 2020)
Immunization is an effort to provide immunity to infants and children by introducing vaccines into the body. In order for the body to make anti-substances to stimulate the formation of anti-substances that are entered into the body by injection (for example, BCG, DPT and measles vaccines) and by mouth (for example, polio vaccine). Immunization is a way to actively increase a person's immunity against an antigen, so that if one is exposed to a similar antigen, disease does not occur. The immunization program aims to reduce morbidity and mortality from diseases that can be prevented by immunization. Currently, these diseases are diphtheria, tetanus, whooping cough (pertussis), measles (measles), polio and tuberculosis (Sudarti, et al. 2012). The participants of this counseling and examination are mothers who have babies aged 0- 11 months who are in the work area of ​​the Midwife Praktik Mandiri Atlantika, A.Md.Keb Tank Seribu, Batam City. Activities include providing material on the meaning and purpose of giving complete basic immunization, schedule for giving immunizations, as well as direct practice of activities for examining the provision of complete basic immunization for babies who get the current immunization schedule. The evaluation of increasing knowledge is done by pre and post test. The results showed that there was a good knowledge of 84.2%, and participants were able to give immunizations for free by being given a schedule again to be given further immunizations. The conclusion of community service in the form of counseling and basic immunization is to increase the knowledge of mothers that it is important to give complete basic immunizations to their babies starting from the time the baby is born, namely from the age of 0-11 months, so that mothers / fathers and the community can better maintain the health of their babies from an early age. By immunizing the baby's body is not susceptible to infectious diseases, immunization is very effective in preventing infectious diseases and immunization can reduce morbidity (morbidity) and mortality (mortality) in children under five.